The effect of competency and orientation toward agripreneurship performance on semi-organic shallot farmers: A case study of Selopamioro Village, Imogiri, Bantul District, Indonesia - Waqingah, S.; Irham, Irham; Mulyo, J. H. (IOP Publishing Ltd, 2022)
The growth of semi-organic shallot farming in Bantul Regency is increasing due to the support of various development programs that are expected to optimize the ability of natural resources as well as building farmer competencies and orientations in order to create independent farmers as agripreneurs. The objectives of the research is to examine the effect of competency and orientation toward agripreneurship performance on semi-organic shallot farmers. This research was conducted purposively in Selopamioro Village as one of the centers for semi-organic shallot development in Bantul Regency. Data were collected through interviews, observations and literature review then analyzed using PLS-SEM. The research showed that the farmers count more on technical and managerial skills than on entrepreneurial orientation. It is found that competency has a positive influence toward agripreneurship performance, which means that the higher the level of competency, the better the agripreneurship performance will be. © Published under licence by IOP Publishing Ltd.